Chronic recurrent emesis in a geriatric patient with jejunal cavernous hemangioma misdiagnosed as diabetic gastroparesis - Li-Yan Liu,; Xun Sun,; Yan Zhu,; Xiang-Wei Meng,; Quan Wang,; Yuan-Jie Sun, (Turkish Journal of Gastroenterology, 2019)
-